Tussle for space: The politics of mock-compliance with global financial standards in developing countries - Florence Dafe; Rebecca Elisabeth Husebye Engebretsen (Regulation & Governance, 2021)
As efforts to harmonize policies globally intensify, developing countries increasingly face pressures to adopt international standards. Yet, we know little about the circumstances under which developing countries manage to circumvent such pressures, or about their strategies to maintain policy space. We explore under which conditions developing countries are willing and able to sustain mock-compliance, a situation where countries comply on paper but not in practice. Using country comparisons of Angola's, Nigeria's, Tanzania's, and Vietnam's engagement with the Basel banking standards, we show how three factors combine to produce sustained mock-compliance: high costs of outright non-compliance due to outward-orientated banking sectors; high political costs of substantive compliance; and state control over profitable markets. Our article contributes to theory-building in the literature on compliance and structural power as well as to broader debates about developing countries' policy autonomy in their engagement with global financial norms.
Keywords: 330; developing countries; financial regulation; policy space; regulatory compliance; structural power